Endoscopic Clipping Versus Suturing for Mucosotomy Closure in E-POEM and G-POEM: A Systematic Review and Meta-Analysis - Yash R. Shah; Ernesto Calderon-Martinez; Dushyant Singh Dahiya; Saurabh Chandan; Manesh Kumar Gangwani; Mihir Shah; Hassam Ali; Amir H. Sohail; Sumant Inamdar; Rashmi Advani (Gastrointestinal Disorders)
Background and Aims: Endoscopic clipping is the standard method for mucosotomy closure in per-oral endoscopic myotomy (POEM) and gastric per-oral endoscopic myotomy (G-POEM). Concerns remain regarding potential leaks and long-term complications. This meta-analysis compares the technical success rates and outcomes of endoscopic clipping and suturing for mucosotomy closure in E-POEM/G-POEM. Methods: A systematic search of databases for studies comparing endoscopic clipping and suturing in E-POEM/G-POEM was conducted. The primary outcomes were technical success rates, and the secondary outcomes were cost, procedure time, and complications. Meta-analyses and sensitivity analysis were performed. Results: Three studies with a total of 91 patients were included. The technical success rates were similar between suturing and clipping, with a success rate of 100% (48/48) for suturing and 94.4% (41/43) for clipping (odds ratio 1.03, 95% confidence interval 0.89–1.19, p = 0.50). There was no significant difference in procedure time between the two methods (SMD −0.73; CI: −1.70 to 0.23; p = 0.13). The cost of suturing was higher on average (mean: $1751, range: $873–$2353) compared to clipping (mean: $898, range: $703–$1083), but the difference was not statistically significant (SMD 1.85, CI −5.05 to 1.35, p = 0.25) with high heterogeneity. Complications for clipping and suturing were also comparable. Conclusions: Both endoscopic clipping and suturing achieve successful mucosotomy closure in E-POEM/G-POEM without any significant difference in the cost and the time between the two closure methods. Further investigation with larger, randomized, controlled trials are necessary to determine their roles in routine practice.